Mandragora autumnalis Distribution, Phytochemical Characteristics, and Pharmacological Bioactivities - Ghosoon Albahri; Adnan Badran; Zaher Abdel Baki; Mohamad Alame; Akram Hijazi; Anis Daou; Joelle Edward Mesmar; Elias Baydoun (Pharmaceuticals)
In the Mediterranean and Himalayan regions, the genus Mandragora (family Solanaceae), sometimes called mandrake, is widely utilized in herbal therapy and is well-known for its mythical associations. Objective: To compile up-to-date information on M. autumnalis’s therapeutic properties. Its pharmacological properties and phytochemical composition are particularly covered in managing several illnesses, including diabetes, cancer, and heart disease. Methods: Articles on the review topic were found by searching major scientific literature databases, such as PubMed, Scopus, ScienceDirect, SciFinder, Chemical Abstracts, and Medicinal and Aromatic Plants Abstracts. Additionally, general online searches were conducted using Google Scholar and Google. The time frame for the search included items released from 1986 to 2023. Results:Mandragora has been shown to contain a variety of phytochemicals, including coumarins, withanolides, and alkaloids. The pharmacological characteristics of M. autumnalis, such as increasing macrophage anti-inflammatory activity, free radicals inhibition, bacterial and fungal growth inhibition, cytotoxic anticancer activities in vivo and in vitro against cancer cell lines, and enzyme-inhibitory properties, are attributed to these phytochemicals. Furthermore, M. autumnalis also inhibits cholinesterase, tyrosinase, α-amylase, α-glucosidase, and free radicals. On the other hand, metabolic risk factors, including the inhibition of diabetes-causing enzymes and obesity, have been treated using dried ripe berries. Conclusions: Investigations into the pharmacological and phytochemical characteristics of M. autumnalis have revealed that this plant is a rich reservoir of new bioactive substances. This review aims to provide insight into the botanical and ecological characteristics of Mandragora autumnalis, including a summary of its phytochemical components and antioxidant, antimicrobial, antidiabetic, anticancer, enzyme-inhibitory properties, as well as toxicological implications, where its low cytotoxic activity against the normal VERO cell line has been shown. More research on this plant is necessary to ensure its efficacy and safety. Still, it is also necessary to understand the molecular mechanism of action behind the observed effects to clarify its therapeutic potential.